Eficiência de biofiltros na qualidade da água em aquicultura - Marques, Viviane dos Santos (2024)
Aquaculture has been experiencing accelerated growth in recent years due to the demand for sustainable food sources and preservation of natural resources. Advances in technologies and management practices have improved efficiency and productivity in aquaculture, contributing economically and environmentally. No water recirculation system (RAS) is continuously recycled and treated to maintain ideal quality, through mechanical and biological filters, in addition, it allows the control of environmental parameters, optimizing various aspects of cultivation. Therefore, the objective of this work is to analyze the influence of different biological filter substrates on maintaining water quality and performance of juvenile Nile tilapia cultivated in RAS. To this end, the study was divided into three chapters, which address the zootechnical performance of Nile tilapia, the physical-chemical quality of the water and the use of eggshell as an alternative substrate for biofilters, respectively. The results obtained were subjected to analysis of variance and a significant effect was selected. The means were compared using the Tukey tests at 5% and Duncan tests at 10% significance. The use of eggshell as a substrate was efficient and stood out among other treatments, providing its economic and environmental predictions when used as a filtering medium, requiring further research into its handling and durability. For CE and SST, values above those recommended by legislation were recorded. For ammonia, critical analyzes were observed up to 30 days, after this period the biofilters reached complete maturation and were efficient in converting ammonia into nitrite and nitrate, maintaining the production levels of these substances at the end of the experiment. It is concluded that all treatments provide satisfactory conditions for performance and water quality, especially those composed of different proportions of clay and gravel, reflecting on the well-being and growth of the animals